Voices from higher up the ladder: exploring the team leader role in call centres - McDonnell, A.; Connell, Julia; Hannif, Z.; Burgess, John (Wiley-Blackwell Publishing, 2013)
This paper focuses on an under-researched employee category in the call centre literature—the team leader. The paper, drawing on data from nine Australian call centres, finds that the team leader role is integral to the effectiveness of call centres, yet it is a role that consists of considerable complexity and contradictions. The research demonstrates the critical role performed by team leaders: coach, mentor, trainer, performance evaluator, communicator and supervisor. It also shows team leaders as being far more positive about many of the features of the call centre work environment compared with those on the front line. However, there does appear to be a need for greater acknowledgement of their challenging role, the contradictions that are inherent in the job and the need, in many cases, for increased support being made available to assist.